2021
DOI: 10.3389/fcell.2021.736298
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenosine RNA Modification: An Emerging Immunotherapeutic Approach to Turning Up Cold Tumors

Abstract: Immunotherapy is a novel clinical approach that has shown clinical efficacy in multiple cancers. However, only a fraction of patients respond well to immunotherapy. Immuno-oncological studies have identified the type of tumors that are sensitive to immunotherapy, the so-called hot tumors, while unresponsive tumors, known as “cold tumors,” have the potential to turn into hot ones. Therefore, the mechanisms underlying cold tumor formation must be elucidated, and efforts should be made to turn cold tumors into ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 148 publications
0
7
0
Order By: Relevance
“…The expression levels of PD-1, PD-L1, HAVCR2, CTLA4, LDHA, LGALS9, TNFRSF18, YTHDF1, LAG3, CD40, TNFRSF4, TNFRSF9, CD86, B2M, and CD8A were higher in Cluster2, whereas PDCD1LG2, IL12A, PVR, and JAK1 were higher in Cluster 2 ( Figure 5D ). Previous studies have shown that high immune scores and activation of suppressive immune checkpoints (like HAVCR2, PD-L1, CTLA-4) play a crucial role in “hot tumors” ( Zhan et al, 2021 ). “Hot tumors” are more likely to benefit from immune checkpoint blockade (ICB) therapy, whereas “cold tumors” with low levels of immune infiltration are more likely to become resistant to immunotherapy ( Galon and Bruni, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The expression levels of PD-1, PD-L1, HAVCR2, CTLA4, LDHA, LGALS9, TNFRSF18, YTHDF1, LAG3, CD40, TNFRSF4, TNFRSF9, CD86, B2M, and CD8A were higher in Cluster2, whereas PDCD1LG2, IL12A, PVR, and JAK1 were higher in Cluster 2 ( Figure 5D ). Previous studies have shown that high immune scores and activation of suppressive immune checkpoints (like HAVCR2, PD-L1, CTLA-4) play a crucial role in “hot tumors” ( Zhan et al, 2021 ). “Hot tumors” are more likely to benefit from immune checkpoint blockade (ICB) therapy, whereas “cold tumors” with low levels of immune infiltration are more likely to become resistant to immunotherapy ( Galon and Bruni, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Tumor development is implicated in the heterogeneity of the TME, such as infiltrating immune cells, extracellular matrix, tumor purity, and non-cellular components ( 65 ). Therefore, we explored the role of the FRL-score in predicting the immune microenvironment landscape of osteosarcoma.…”
Section: Resultsmentioning
confidence: 99%
“…There is convincing evidence [13] that m 6 A occurring on mRNA plays an indispensable role in the function of immune cells and innate immune response in the tumor microenvironment. First, we analyzed the correlation of 51 genes [21] encoding immunomodulatory molecules with risk scores and found that these genes were highly expressed in most of the high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…M 6 A methylation modi cation is a dynamically reversible modi cation process that is mainly regulated by m 6 A methyltransferase complexes (writers) such as METTL3, m 6 A demethylases (erasers) such as ALKBH5, and m 6 A binding proteins (readers) such as YTHDC1 [11]. Recently, it has been shown that m 6 A plays an important role in the tumor immune microenvironment (TIME), providing new ideas for clinical immunotherapy [12,13]. However, the m 6 A level and TIME in digestive system pancancer patients with a high incidence of venous thrombosis remain ambiguous.…”
Section: Introductionmentioning
confidence: 99%